Promyelocytic Leukemia Protein Is an Essential Regulator of Stem Cell Pluripotency and Somatic Cell Reprogramming - Hadjimichael, Christiana (Stem Cell Reports, 2017)
Promyelocytic leukemia protein (PML), the main constituent of PML nuclear bodies, regulates various physiological processes in different cell types. However, little is known about its functions in embryonic stem cells (ESC). Here, we report that PML contributes to ESC self-renewal maintenance by controlling cell-cycle progression and sustaining the expression of crucial pluripotency factors. Transcriptomic analysis and gain- or loss-of-function approaches showed that PML-deficient ESC exhibit morphological, metabolic, and growth properties distinct to naive and closer to the primed pluripotent state. During differentiation of embryoid bodies, PML influences cell-fate decisions between mesoderm and endoderm by controlling the expression of Tbx3. PML loss compromises the reprogramming ability of embryonic fibroblasts to induced pluripotent stem cells by inhibiting the transforming growth factor β pathway at the very early stages. Collectively, these results designate PML as a member of the regulatory network for ESC naive pluripotency and somatic cell reprogramming.